2011
DOI: 10.1097/bsd.0b013e3181f7cc9f
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Posterolateral Transmuscular Approach for Lumbar Foraminal Stenosis

Abstract: Posterolateral transmuscular approach with microsurgical foraminotomy provided excellent surgical results. Coronal thin-sliced MRI can be useful for diagnosis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 15 publications
1
24
0
4
Order By: Relevance
“…Inferior partial pediculectomy can be performed to achieve adequate decompression [1][2][3][4][5][6].…”
Section: Mefd Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Inferior partial pediculectomy can be performed to achieve adequate decompression [1][2][3][4][5][6].…”
Section: Mefd Groupmentioning
confidence: 99%
“…For surgical treatment of lumbar foraminal stenosis (LFS), recent studies have demonstrated the efficacy of microsurgical extraforaminal decompression (MeFD) [1][2][3][4][5][6]. This procedure involves unroofing of the stenotic foramen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al [15] also demonstrated that the course became distorted and crank shaped, with the middle section elevated cranially and pushed against the caudal aspect of the pedicle of the cranial vertebra, as observed via coronal MRI. As a morphologic change, this phenomenon might be similar to our findings.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, assessing the precise position of the stenosis inside or outside the lumbar spinal canal is important for surgeons, who must choose either extraspinal or intraspinal canal decompression as the appropriate surgical approach [12]. Various methods, such as selective lumbar nerve block [13], electrophysiological methods [14], three-dimensional computed tomography scan [11], and magnetic resonance imaging (MRI) of sagittal sections [1,15], have been suggested to prevent incorrect diagnoses. However, some of these methods can be problematic because of their complexity or lack of sensitivity and specificity (eg, conventional MRI, 93% and 52%, respectively) [16].…”
Section: Introductionmentioning
confidence: 99%